Integrative description of a new Tunisian tardigrade species, Macrobiotus azzunae sp. nov. (Eutardigrada, Macrobiotidae, hufelandi group) - Ben Marnissi, Jamila; Cesari, Michele; Rebecchi, Lorena; Bertolani, Roberto (European Journal of Taxonomy, 2021)
In this paper a new tardigrade species, Macrobiotus azzunae sp. nov., from Tunisia, is described. An integrative taxonomic approach was applied by combining morphological, morphometric and molecular data. In particular, light and scanning electron microscopy observations, and four genetic markers, three nuclear (18S rRNA, 28S rRNA and ITS-2) and one mitochondrial (COI) were used. The analysis showed that M. azzunae sp. nov. belongs to the Macrobiotus hufelandi group and is most similar to Macrobiotus sandrae Bertolani & Rebecchi, 1993. It differs from M. sandrae by a more pronounced constriction of the first macroplacoid (hardly visible in M. sandrae) and for the eggshell shape, with thinner wires of the reticulum and meshes around the processes larger than the inter-process meshes in M. azzunae sp. nov., while all meshes are similar in size in M. sandrae. The species is gonochoristic. With this discovery, there are 33 species of tardigrades identified in Tunisia, all non-marine. This result, compared with nearby Sicily, where more research has been conducted, indicates that there is a considerable potential for identification of new species. Further research will be most informative if multiple habitats are explored and if carried out with an integrated approach as done in this present work.